CHEMICAL PROPERTIES OF SOIL IN QUARTZ SAND MINING IN RIAU ISLANDS PRE-RECLAMATION ACTIVITIES: SIFAT KIMIA TANAH PADA TAMBANG PASIR KUARSA DALAM KEGIATAN PRA REKLAMASI KEPULAUAN RIAU - Dita Irwanti Pratiwi; Mohammad Nurcholis (INTAN Jurnal Penelitian Tambang, 2023)
It is necessary to figure out the chemical characteristic of soil in the pre-reclaimed land of quartz sand mines in order to find the appropriate and optimal reclamation method applied. A laboratory analysis is then conducted to determine the impact of the causes of decreased soil fertility. This research is conducted at PT. X Kepulauan Riau. The method used for soil sampling is FAO (1976) at a depth of 0-30 cm, with a total of 4 samples, namely sample A, B, C, and D. Sample A, B, and C are used in the XRF (X-Ray Fluorescence) method to determine the chemical compounds contained in the soil, while sample D is used for analyzing the soil chemical characteristic to determine the nutrients contained in the soil. Based on the results of the analysis, the condition of the pre-reclaimed land of quartz sand is classified as infertile. Nutrient levels in the pre-reclaimed land were mostly low, and this is an important factor inhibiting plants from growing at the study site.